2015
DOI: 10.4049/jimmunol.1403004
|View full text |Cite
|
Sign up to set email alerts
|

Acute Viral Respiratory Infection Rapidly Induces a CD8+ T Cell Exhaustion–like Phenotype

Abstract: Acute viral infections typically generate functional effector CD8+ T cells (TCD8) that aid in pathogen clearance. However, during acute viral lower respiratory infection (LRI), lung TCD8 are functionally impaired and do not optimally control viral replication. T cells also become unresponsive to antigen during chronic infections and cancer via signaling by inhibitory receptors like programmed cell death-1 (PD-1). PD-1 also contributes to TCD8 impairment during viral LRI, but how it regulates TCD8 impairment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 66 publications
2
30
2
Order By: Relevance
“…This is in contrast to splenic or draining lymph node T CD8 , which maintain functionality during respiratory viral infection (1924, 38). Here, we confirmed that splenic T CD8 remain functional at later time points; we focused on splenic T CD8 because transcriptome analyses showed significant differential gene regulation between lung and spleen T CD8 (45). Moreover, there were insufficient numbers of cells in the draining lymph nodes during HMPV infection to perform ex vivo tetramer and ICS assays (data not shown).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This is in contrast to splenic or draining lymph node T CD8 , which maintain functionality during respiratory viral infection (1924, 38). Here, we confirmed that splenic T CD8 remain functional at later time points; we focused on splenic T CD8 because transcriptome analyses showed significant differential gene regulation between lung and spleen T CD8 (45). Moreover, there were insufficient numbers of cells in the draining lymph nodes during HMPV infection to perform ex vivo tetramer and ICS assays (data not shown).…”
Section: Discussionsupporting
confidence: 66%
“…Gene expression analysis of lung and spleen T CD8 revealed that numerous immunomodulatory receptors were upregulated by lung T CD8 during acute viral LRI (45). To determine whether some of these inhibitory receptors increased on the cell surface during acute viral LRI, we performed flow cytometric analysis of lung and spleen HMPV-specific T CD8 at days 7, 10, and 14 p.i.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the level of residual antigen presentation must be lower than that exhibited during a typical chronic infection. In line with this, PD-1 as well as other potential inhibitory molecules may act to prevent excessive immunopathology (26,27,29) by maintaining the cells in a quiescent state (49). Furthermore, reactivation of CD8 + T RM cells in the lung leads to sustained expression of interferon-induced transmembrane protein (IFITM3), which is involved in conferring resistance against subsequent virus infection (132).…”
Section: Maintenance Of Lung Cd8 + T Rm Cellsmentioning
confidence: 93%
“…Erickson and coworkers recently extended the understanding of the mechanisms responsible for impaired CTL responses in the respiratory tract of mice acutely infected with HMPV. They demonstrated that upon antigen recognition in the lungs, CD8 ϩ T cells rapidly become exhausted due to the upregulation of PD-1 and other inhibitory receptors (223). Therefore, the infection-generated immunological milieu appears to dampen the efficient clearance of HMPV in vivo.…”
Section: Acquired Immunity To Hmpv Infection and Contribution To Pathmentioning
confidence: 99%
“…Animal studies have contributed enormously to the preclinical evaluation of vaccine candidates and helped in the identification of immunological mechanisms that confer immunity against experimental infections (summarized in Table 1) (85,91,97,103,126,227,229,230,(232)(233)(234)(235)(236)(237)(238)(239). At the molecular level, the mouse model of infection has yielded the majority of evidence regarding potential pathophysiological mechanisms related to HMPV lung disease (132,138,148,159,160,220,223,240,241). Despite this body of information, however, a debate has been raised regarding the usefulness of the mouse model in understanding the response of humans against HMPV.…”
Section: Animal Models For the Study Of Hmpv-induced Pathogenesismentioning
confidence: 99%